An Update on the Status of Sponsored Research in Counseling Psychology. (May 2016) - Martens, Matthew P.; Herman, Keith C.; Takamatsu, Stephanie K.; Schmidt, Lexi R.; Herring, Tracy E.; Labuschagne, Zandre; McAfee, Nicholas W.
Prior research has indicated that relative to other specialty areas in psychology, counseling psychology researchers are less likely to engage in research activities sponsored by external funding agencies. The primary purposes of this article were to address external funding in the counseling psychology profession and to compare the rates of articles published in the premier counseling psychology research journal ( Journal of Counseling Psychology [ JCP ]) that reported external funding to other specialty areas' premier research journals. Between 2007 and 2011, articles in JCP were less likely than those in other journals to report external funding and less likely to report research designs associated with external sponsorship. Post hoc analyses indicated that articles in a leading vocational research journal also had relatively low rates of external funding, and counseling psychology faculty members were less likely than peers in other programs to report external funding. The implications of these findings for the field are discussed.